2008
DOI: 10.2139/ssrn.1137166
|View full text |Cite
|
Sign up to set email alerts
|

The Computational Generative Patterns in Indonesian Batik

Abstract: The paper discusses the terminology behind batik crafting and showed the aspects of self-similarity in its ornaments. Even though a product of batik cannot be reduced merely into its decorative properties, it is shown that computation can capture some interesting aspects in the batik-making ornamentation. There are three methods that can be exploited to the generative batik, i.e.: using fractal as the main source of decorative patterns, the hybrid batik that is emerged from the acquisition of L-System Thue-Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…As it has already been discussed in [10], traditionally Indonesian Batik has shown interesting fractal geometry while it has also been demonstrated that this property could broaden the acquisition of batik as model to generative art rooted from the traditional heritage. While we have recognized the steps of making the batik crafts [3], the computations of the innovative landscape of batik designs are now providing borderless creations of design applicable to enrichment the available traditional motif 1 .…”
Section: Introductionmentioning
confidence: 79%
“…As it has already been discussed in [10], traditionally Indonesian Batik has shown interesting fractal geometry while it has also been demonstrated that this property could broaden the acquisition of batik as model to generative art rooted from the traditional heritage. While we have recognized the steps of making the batik crafts [3], the computations of the innovative landscape of batik designs are now providing borderless creations of design applicable to enrichment the available traditional motif 1 .…”
Section: Introductionmentioning
confidence: 79%
“…the creativity of each batik designer to decide the usage of the generative motifs, be it as klowongan, isen-isen, or harmonization ornamentation, in his batik design (cf. Situngkir, 2008). The latter is highly related to the classifications and standard batik be it the mbatik conventions in keraton or the highly external influence of coastal cities (Sondari & Yusmawati, 2000).…”
Section: Figurementioning
confidence: 99%
“…It is also possible to generate Batik motifs and ornamentation -which found has a fractal property in its complex geometry -computationally. Situngkir (2008) have been classified innovation types of batik motifs and found that batik motif could growth computationally by incorporating fractal generation algorithm, such as iterated function system, complex plane, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The first is interesting since batik has been widely recognized even in international stages as signature of Indonesian fashion. Batik depicts the complexity related to not only the processes of ornamentation and the related usages in (Javanese) specific occasions but also places where the unique batik is crafted: the palace-centric (keraton) batik and those which produced in creative industries of coastal areas in Java [11].…”
Section: Figurementioning
confidence: 99%